Physical and mechanical properties of the nanocomposite and combined Ti-N-Si /WC-Co-Cr and Ti-N-Si/(CR3C2)75-(NiCr)25 coatings - O.V. Kolisnichenko; N.A. Makhmudov; N.K. Erdybayeva; V.M. Beresnev; G.V. Kirik; A.V. Pshyk; A.P. Shypylenko; M.V. Kaverin; M.V. Il’yashenko; A.D. Pogrebnjak; Yu.N. Tyurin; A.P. Shpak (Журнал нано- та електронної фізики)
Two types of the combined nanocomposite coatings (Ti-N-Si /WC-Co-Cr and Ti-N-Si/ (Cr3C2Ni)75-(NiCr)25) of 160-320 μm thickness were produced using two deposition techniques: the cumulative-detonation and the vacuum-arc deposition with the high-frequency discharge. This gives the possibility (using the combined coatings) to restore the size of worn areas of the tools and demonstrate the high corrosion and wear resistance, to increase the hardness, modulus of elasticity, and plasticity index. Composition of the top coating varied from Ti = 60 at.%, N = 30 at.%, and Si = 10 at.% to Ti = 75 at.%, N = 20 at.%, and Si = 5 at.%. In the first series of coatings the following phases were obtained: (Ti;Si) and TiN in thin top coating and WC and W2C in thick bottom coating. The second series gives (Ti;Si)N and TiN in top coating; Cr3Ni2 and pure Cr in bottom coating; and small amount of Ti19O17 in the transition region between thin and thick coatings. For the first series the grain size achieved 25 nm at the hardness of 38 GPa. For the second series the grain size was 15 nm at the hardness of 42 GРa ± 4 GPa. It is shown that the corrosion resistance in salt solution and acid media increases with the wear decrease as a result of the cylinder friction over the surface of combined coating.